PERBEDAAN KADAR ZINC DAN KEJADIAN ISPA SERTA KEJADIAN DIARE PADA BALITA STUNTING-WASTING DAN BALITA NORMAL DI PUSKESMAS NANGAPANDA KABUPATEN ENDE - YUSTINA PACIFICA MARIA PASCHALIA (JURNAL INFO KESEHATAN, 2014)
Stunting describes the state of longstanding malnutrition that takes time for children to grow and recover, while wasting can occur due to the period of a state of malnutrition which is relatively short and which can be recovered quickly. Several studies have shown that zinc deficiency affects the growth of hormone. Severe zinc deficiency weakens the immune function, was eventually increased susceptibility to infection, including respiratory infection and diarrhea. The objective of this reserch was to study and analysis the differences in zinc levels, the incidence of respiratory infection and diarrhea in the stunting-wasting children and normal children. The study was an analytical observational study, design for a comparative study using cross sectional approach, was conducted in the area of Nangapanda-Ende Regency. The study sample consisted of two groups of children 2-5 years old suffering from stunting-wasting and normal children. The research result showed there was no difference in zinc levels between stunting-wasting children groups and normal children groups (p=0,117). There were also differences in the incidence of respiratory infection in the stunting-wasting children and normal children (p=0,000). There were also differences in the incidence of diarrhea in the stunting-wasting children and normal children (p=0,000). Conclusion: There was a correlation between zinc levels with the incidence of respiratory infection in stunting-wasting children and normal children. There was a correlation between zinc levels with the incidence of diarrhea in stuntingwasting children and normal children.